High-pressure phases of SF6 up to 32 GPa from X-ray diffraction and Raman spectroscopy. (May 2015) - Rademacher, N.; Friedrich, A.; Morgenroth, W.; Bayarjargal, L.; Milman, V.; Winkler, B.
Abstract: X-ray diffraction and Raman spectroscopy were employed to study the phase diagram of SF6 at pressures up to 32 GPa. The known phase transformation of SF6 phase I to phase II at around 2 GPa was confirmed. Discontinuities in the pressure dependence of the Raman frequencies and positions of X-ray reflections indicate further phase transitions at 10(1) and 19(1) GPa. The crystal structures of phases I and II were determined using single crystal X-ray diffraction. The structure of phase I corresponds to the "plastic" body-centred cubic low-temperature structure and the structure of phase II to the ordered monoclinic low-temperature structure. The bulk moduli of phase I and II were determined to be B 0, I = 6.3 ( 2 ) GPa with B I ′ = 4 (fixed) and B 0, II = 8.5 ( 8 ) GPa with B II ′ = 7.4 ( 9 ), respectively. The linear compressibilities of phase II showed a slight anisotropy, which can be rationalised by consideration of the packing of the SF6 molecules. Abstract : Highlights: Crystal structures of SF6 phase I and II at high pressures were determined. The bulk moduli of phase I and II were determined. Raman and X-ray diffraction indicate further phase transformations at high pressures.